Pengembangan Desa Wisata Molinow Di Kecamatan Tenga Kabupaten Minahasa Selatan - Kezia Aneke Indah Lamia; Joyce Rares; Femmy Tulusan (Sam Ratulangi University, 2023)
Abstract The purpose of this study is to find out how the development of tourism objects, namely the Molinow tourist village in Tenga District, South Minahasa Regency. This research uses a descriptive method with a qualitative approach. The development of tourism can be seen from two important aspects, namely tourist attraction attractions and information and promotion. Data collection was carried out through observation, interviews, and literature studies with analysis model data analysis techniques by Miles and Huberman. Based on the results of the study, judging from the attractions of tourist attractions, there are still several criteria or standards that have not met the standards of the arrangement of tourist attractions and recreational recreational facilities are not adequate, besides that there are no souvenirs for visitors. Furthermore, efforts to promote tourism potentials in Molinow village through the JADESTA (Tourism Village Network) Pesona Indonesia website, as well as through social media. The problem is that promotional efforts only at certain times are not intensely carried out. Key Words : development, tourist villages